FUNGSI HUKUM PIDANA INTERNASIONAL TERHADAP KEJAHATAN INTERNASIONAL - Wulandari, Anita; Fath, Ratu Adnindha Agnienqie An Romadhani Nur; Agustiawan, M. Nassir (LPPM Universitas Bina Bangsa, 2024)
Basically, when studying international criminal law, the most important thing is that we have to understand the meaning of criminal law itself, the meaning of criminal law, namely, the rules that regulate a person's behavior and in criminal law it also regulates what criminal acts are prohibited, and there are sanctions for them. criminal acts are committed so that when there are rules and sanctions, people become reluctant to commit prohibited criminal acts, thereby creating social order and peace in society. In a broader scope, there is international criminal law which regulates relations between countries within the scope of international society. Because its scope is broader, international criminal law is cross-border in nature, in which there is cooperation between countries in preventing and eradicating crime. With the existence of international criminal law, expanding information regarding crimes not only within the country but also abroad shows the world that there are criminal acts that violate the law and morals. So that international criminal law is international legal principles and rules, not national or domestic